Answer:
Explanation:
Several trig identities are involved in the proof of this. This is the order in which they are used.
- cos(2x) = cos²(x) -sin²(x)
- cos²(x) +sin²(x) = 1
- cos(x) = 1/sec(x)
Proof
Starting with the left side, we can transform it into the right side.
![2\cos(2x)=2(\cos^2(x)-\sin^2(x)) = 2(\cos^2(x)-(1-\cos^2(x)))\\\\=2(2\cos^2(x)-1)=2\left((2)/(\sec^2(x))-(\sec^2(x))/(\sec^2(x))\right)\\\\=\boxed{(4-2\sec^2(x))/(\sec^2(x))}](https://img.qammunity.org/2023/formulas/mathematics/college/z6eupd6n5jx69n40gqnd5ge0mhpz8yqzbl.png)